Mini-review: Angiotensin- converting enzyme 1 (ACE1) and the impact for diseases such as Alzheimer’s disease, sarcopenia, cancer, and COVID-19 - Bueno, Valquiria; Frasca, Daniela (Frontiers in Aging, 2023)
Ageing has been associated with comorbidities, systemic low-grade of inflammation, and immunosenescence. Hypertension is the most common morbidity and anti-hypertensives are used for more than 50%. Angiotensin-converting enzyme 1 inhibitors (ACEi) and angiotensin II receptor blockers (ARB) control blood pressure but also seem to play a role in comorbidities such as Alzheimer’s disease, sarcopenia and cancer. The impact of anti-hypertensives in comorbidities is due to the expression of renin-angiotensin-system (RAS) in several tissues and body fluids. Angiotensin-converting enzyme 1 (ACE1) has been linked to oxidative stress, metabolism, and inflammation. The levels and activity of ACE1 are under genetic control and polymorphisms have been correlated with susceptibility to Alzheimer’s disease. In addition, some results found that ACEi and ARB users present delayed cognitive decline and reduced risk of dementia. Regarding to sarcopenia, RAS has been linked to the catabolic and anabolic pathways for muscle mass maintenance. In some studies, older adults using ACEi were highly benefited by exercise training. In cancer, RAS and its products have been shown to play a role since their inhibition in animal models modulates tumor microenvironment and improves the delivery of chemotherapy drugs. Clinically, the incidence of colorectal cancer is reduced in patients using ACEi and ARB. During the pandemic COVID-19 it was found that ACE2 receptor plays a role in the entry of SARS-CoV-2 into the host cell. ACE1 genotypes have been linked to an increased risk for COVID-19 and severe disease. In some studies COVID-19 patients taking ARB or ACEi presented better outcome.